2010
DOI: 10.1007/7854_2010_60
|View full text |Cite
|
Sign up to set email alerts
|

Eye Tracking Dysfunction in Schizophrenia: Characterization and Pathophysiology

Abstract: Eye tracking dysfunction (ETD) is one of the most widely replicated behavioral deficits in schizophrenia and is over-represented in clinically unaffected first-degree relatives of schizophrenia patients. Here, we provide an overview of research relevant to the characterization and pathophysiology of this impairment. Deficits are most robust in the maintenance phase of pursuit, particularly during the tracking of predictable target movement. Impairments are also found in pursuit initiation and correlate with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 221 publications
(302 reference statements)
4
91
1
2
Order By: Relevance
“…This finding is compatible with evidence of motion processing deficits during smooth pursuit in schizophrenia patients. 122,134 Higher levels of both positive and negative schizotypy are also associated with an increased rate of direction errors on the antisaccade task. [126][127][128][129]135 Recently, an fMRI study investigated the neural underpinnings of this deficit in relation to positive schizotypy.…”
Section: Motor Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is compatible with evidence of motion processing deficits during smooth pursuit in schizophrenia patients. 122,134 Higher levels of both positive and negative schizotypy are also associated with an increased rate of direction errors on the antisaccade task. [126][127][128][129]135 Recently, an fMRI study investigated the neural underpinnings of this deficit in relation to positive schizotypy.…”
Section: Motor Controlmentioning
confidence: 99%
“…These studies originated in the observations of impairments in schizophrenia on a range of eye movement paradigms, including most prominently the smooth pursuit and antisaccade tasks. 122,123 Extending this work, there is now considerable evidence of associations of higher schizotypy with impaired performance on smooth pursuit (following a slowly moving target) [124][125][126][127] and antisaccades (making a rapid eye movement in the direction opposite to a sudden-onset peripheral target). [127][128][129] Pursuit deficits, which have been observed in both positive and negative schizotypy, 125,126 involve a reduced ability to match eye velocity to target velocity.…”
Section: Motor Controlmentioning
confidence: 99%
“…SPEM are relatively slow movements of the eye (usually less than 100 degrees per second). In contrast to saccadic movements, which aim to bring an object onto the fovea quickly, SPEM consists of a pursuit and a 'catch-up' phase, which acts to keep the object on the fovea throughout movement [15].…”
Section: Smooth Pursuit Eye Movements (Spem)mentioning
confidence: 99%
“…During SPEM tasks, patients with schizophrenia tend to make more intrusive saccadic movements than nonpsychiatric controls, potentially reflecting deficits in predictive and motion processing [15]. A functional magnetic resonance imaging (fMRI) study evaluating brain activation during a simple SPEM task showed greater activation of the posterior hippocampi and fusiform gyrus during the task, along with decreased activation in the frontal eye fields and occipital cortex [16].…”
Section: Smooth Pursuit Eye Movements (Spem)mentioning
confidence: 99%
“…32,33 Specific genes, such as RGS4 and the catechol-O-methyltransferase (COMT) gene, have been suggested as genetic links between schizophrenia and eye tracking, 34,35 but no gene or chromosomal region has been conclusively implicated. Specific genetic defects have also been proposed to explain the occurrence of strabismus in schizophrenia 36,37 and the protective effect of congenital cortical blindness. 27 An ancillary, though not mutually exclusive, explanation for the occurrence of eye abnormalities in schizophrenia is infectious agents in the eye and/or central nervous system.…”
Section: Possible Explanationsmentioning
confidence: 99%